Lesión por estiramiento de los músculos esqueléticos: Estudio experimental con el músculo soleus de ratas - Pachioni, Célia Aparecida Stellutti [UNESP]; Mazzer, Nilton; Barbieri, Claudio Henrique; de Camargo, Marcela Regina [UNESP]; Fregonesi, Cristina Elena Prado Teles [UNESP]; do Carmo, Edna Maria [UNESP]; Nozabielli, Andrea Jeanne Lourenço [UNESP]; Martinelli, Alessandra Rezende [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
The study aimed to verify the physiological injury behavior by stretching the soleus muscle of rats, using a noninvasive experimental model. Twenty-four rats were used and divided into three groups of eight animals: control group (A), group that performed tetanus followed by electrical stimulation and a sudden dorsiflexion of the left paw performed by a device equipped with a mechanism of muscle soleus rapid stretching (B); and a group that only received the tetanus (C). Three days later, the animals were killed, and the soleus muscle was resected and divided into three segments. Morphological changes indicative of muscle damage appeared in all three segments of group B. In a lesser degree, similar changes were also detected in muscles subjected to only tetanus. This model was effective; reproducing an injury similar to what occurs in human sports injuries.
Stretch injuries of skeletal muscles: Experimental study in rats' soleus muscle
Keywords: Animal; Disease models; Rats; Skeletal muscle; Tetany